2015
DOI: 10.1095/biolreprod.115.129643
|View full text |Cite
|
Sign up to set email alerts
|

From Somatic Cells to Oocytes: A Novel Yolk Protein Produced by Ovarian Somatic Cells in a Stony Coral, Euphyllia ancora1

Abstract: To gain a better understanding of how corals form their eggs at both the molecular and cellular levels, we performed a differential screen (suppression subtractive hybridization) to identify genes related to oocyte development in a stony coral, Euphyllia ancora. Through the course of screening, a novel gene that contains three alternate repeats of fibronectin domain 2 and epidermal growth factor (EGF)-like domains, as well as an additional calcium-binding EGF-like domain (EGF-CA), was identified and tentativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…However, few studies have examined the characteristics and function of gonadal somatic cells in corals. Previously, the authors of the present study have found that several types of yolk proteins are produced by the ovarian somatic cells adjacent to oocytes and are then transported to and accumulate in oocytes during oogenesis in the stony coral Euphyllia ancora (Shikina, Chiu, Lee, & Chang, 2015;Shikina et al, 2013). These findings clearly demonstrate that gonadal somatic cells are specialized to support oocyte development and play a crucial role in coral oogenesis.…”
supporting
confidence: 73%
“…However, few studies have examined the characteristics and function of gonadal somatic cells in corals. Previously, the authors of the present study have found that several types of yolk proteins are produced by the ovarian somatic cells adjacent to oocytes and are then transported to and accumulate in oocytes during oogenesis in the stony coral Euphyllia ancora (Shikina, Chiu, Lee, & Chang, 2015;Shikina et al, 2013). These findings clearly demonstrate that gonadal somatic cells are specialized to support oocyte development and play a crucial role in coral oogenesis.…”
supporting
confidence: 73%
“…Upregulated genes in premature/mature ovaries Yolk formation and accumulation is one of the most important aspects of oogenesis for oviparous animals. In scleractinian eggs, several major yolk proteins, including vitellogenin (Vg), a female-speci c phosphoglycolipoprotein, and large amounts of lipids (e.g., wax esters, fatty acids, phosphatidylethanolamines, and phosphatidylcholines) have been identi ed to date [12,13,19,20,38,39]. The present study found that transcripts encoding 3 major yolk proteins were upregulated (Vg, Egg protein, and Euphy, Fig.…”
Section: Scleractinian Gonadal Transcriptome Assemblymentioning
confidence: 54%
“…The Notch signaling pathway is conserved across animal taxa, and regulates cell-cell interactions and cell fate determination [60]. One of the identi ed genes, neurogenic locus notch homolog protein 1, encodes Euphy, a novel major yolk protein in E. ancora oocytes identi ed in our previous study [13]. The remaining 2 genes have not been previously reported.…”
Section: Scleractinian Gonadal Transcriptome Assemblymentioning
confidence: 92%
“…Sexes of the source colonies were unable to be determined due to difficulty in identifying sex in this species. No enriched GO terms related to oogenesis or reproduction were identified, but examining the abundance of proteins associated with oocyte development (vitellogenin and egg protein) (25) revealed that these protein abundances were slightly higher in N-corals than Ocorals (SI.2H), suggesting reproduction as an unlikely cause of lipid increase in O-corals.…”
Section: Resilient Physiological Traits In the Nearshore Coralsmentioning
confidence: 99%